Efficacy of the Combined Administration of Systemic and Intra-Articular Tranexamic Acid in Total Hip Arthroplasty Secondary to Femoral Neck Fracture: A Retrospective Study. (25th April 2020) - Maalouly, Joseph; Tawk, Antonios; Ayoubi, Rami; Al Rahbani, Georges Katoul; Metri, Aida; Saidy, Elias; El-Hajj, Gerard; Nehme, Alexandre
Abstract : Background . Total hip arthroplasty (THA) is associated with substantial blood loss in the postoperative course. Tranexamic acid (TXA) is a potent antifibrinolytic agent, routinely administered by intravenous (IV) and topical (intra-articular, IA) route, which can possibly interrupt the cascade of events due to hemostatic irregularities close to the source of bleeding. However, scientific evidence of combined administration of TXA in THA secondary to a femoral neck fracture is still meagre. The present study aims to compare the patients who were administered combined IV and topical TXA with a control group in terms of blood loss, transfusion rate, and incidence of deep vein thrombosis (DVT) and thromboembolism (TE). Patients and Methods . 195 patients with femoral neck fracture underwent THA and were placed into two groups: (1) IV and IA TXA group which had 58 patients and (2) no TXA control group which had 137 patients. In the TXA group, 1 g IV TXA was administered 30 minutes before incision, and 1 g IA TXA was administered intraoperatively after fascia closure. No drains were placed, and soft spica was applied to the hip. Results . Combined usage of IV and IA TXA showed better results when compared to the control group in terms of blood transfusion rate (31%) and hemoglobin drop (28%). No cases of DVT or TE were noted among the two study groups. Conclusion . Combined use of IV and IA TXA provided significantly better results compared to no TXA use with respect to all variables related to postoperative blood loss in THA. Moreover, TXA use is safe in terms of incidence of symptomatic DVT and TE.